Heal your gut cookbook nutrient-dense recipes for intestinal health using the GAPS diet - Boynton, Hilary; Brackett, Mary G. (White River Junction, Vermont Chelsea Green Publishing, 2014)
Gut and Psychology Syndrome (GAPS) refers to disorders, including ADD/ADHD, autism, addictions, depression, and obsessive-compulsive disorder, stemming from or exacerbated by leaky gut and dysbiosis. GAPS also refers to chronic gut-related physical conditions, including celiac disease, rheumatoid arthritis, diabetes type one, and Crohn's disease, as well as asthma, eczema, allergies, thyroid disorders, and more. The authors offer encouraging, real-life perspectives on the life-changing improvements to the health of their families by following this challenging, but powerful, diet.
Before you begin the GAPS diet -- The GAPS introduction diet -- The full GAPS diet.
Includes bibliographical references (pages 289-294) and index.
111060
Keywords: Gastrointestinal system -- Diseases -- Diet therapy; Cooking for the sick; Cooking -- Health & Healing -- Low Carbohydrate; Health and Fitness -- Diets; Medical -- Nutrition; Cookbook; Health